2021
DOI: 10.1007/s00248-020-01667-7
|View full text |Cite
|
Sign up to set email alerts
|

Root-Associated Mycobiomes of Common Temperate Plants (Calluna vulgaris and Holcus lanatus) Are Strongly Affected by Winter Climate Conditions

Abstract: Winter temperatures are projected to increase in Central Europe. Subsequently, snow cover will decrease, leading to increased soil temperature variability, with potentially different consequences for soil frost depending on e.g. altitude. Here, we experimentally evaluated the effects of increased winter soil temperature variability on the root associated mycobiome of two plant species (Calluna vulgaris and Holcus lanatus) at two sites in Germany; a colder and wetter upland site with high snow accumulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…A similar dynamic was observed between ericoid mycorrhizal fungi and members of Mucoromycota in a recent mesocosm experiment with the shrub Calluna vulgaris where the soil was exposed to winter pulse‐freezing treatments, resulting in a strong decrease of the mycorrhizal symbiont and a high increase in Mucoromycota sp. (Borg Dahl et al, 2021). Taken together with our observations, this suggests that a similar dynamic occurs in our S− treatment; unfortunately, no quantitative measures of EcM biomass are available to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar dynamic was observed between ericoid mycorrhizal fungi and members of Mucoromycota in a recent mesocosm experiment with the shrub Calluna vulgaris where the soil was exposed to winter pulse‐freezing treatments, resulting in a strong decrease of the mycorrhizal symbiont and a high increase in Mucoromycota sp. (Borg Dahl et al, 2021). Taken together with our observations, this suggests that a similar dynamic occurs in our S− treatment; unfortunately, no quantitative measures of EcM biomass are available to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, intense freeze–thawing is a lethal threat to microorganisms due to frost dehydration and cell rupture (Jefferies et al, 2010; Schimel et al, 2007; Shchepin et al, 2014). A recent mesocosm experiment found the strong response to altered winter temperature conditions in the soil microbial community composition, which was interlinked to changes in the nutrient dynamic and plant growth in the following season of two common temperate plant species ( Calluna vulgaris and Holcus lanatus ; Borg Dahl et al, 2021). Additionally, plant–soil interaction models predict a faster response to environmental changes among soil microbes than among primary producers, for example, forest trees, with the former likely undergoing a community reordering prior to the latter (Bardgett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both Rozellomycota and Chytridiomycota fungi belong to the Zoosporic phyla with motile spores, which typically play critical ecological roles in the recycling of energy and matter in food webs [102]. As fast growing saprotrophic fungi, the Mortierellomycota phyla are potentially influenced by soil temperature [103] and have important biological functions for the protection of plants against pathogens [104]. Interestingly, Mucoromycota fungi may be utilized as a biorefinery that employs fungi for its highly versatile metabolic system, which can generate several valuable bioproducts including of pigments, polyphosphates, ethanol, organic acids, enzymes, as well as lowand high-value lipids [105,106].…”
Section: Discussionmentioning
confidence: 99%
“…Droughts can also delay or reduce the flowering period (Jentsch et al 2009;Nagy et al 2013). It has been shown that drought affects the Calluna root-associated mycobiome, with as yet unknown consequences for the plants' vitality, soil nutrient processes and heathland productivity (Dahl et al 2021;Tobermann et al 2008).…”
Section: Calluna Recruitment Response To Drought and High Airborne Ni...mentioning
confidence: 99%